Trends in Chinese value chains 2018-2022 - Heli Simola (Bank of Finland, Bank of Finland Institute for Emerging Economies (BOFIT), 2023)
We examine recent changes in the structure of Chinese manufacturing value chains using a standard input-output framework. Our results suggest that the previous increasing trend in the share of domestic value added in Chinese value chains stalled during our observation period (2018-2022). We also note a shift in the geographic structure of foreign value added embodied in Chinese value chains. These changes seem to be mainly associated with trade policy measures implemented by China and other countries. China's share has increased in the foreign value added embodied in manufacturing value chains of the US, EU and Russia.
urn:nbn:fi-fe20231018140600
Keywords: 330; value-added trade; global value chains; fragmentation; input-output; China